Option d: 3 with multiplicity 4 and –6 with multiplicity 2
Explanation:
The function is [tex]f(x)=(x-3)^4(x+6)^2[/tex]
To determine the roots of a polynomial, let us substitute [tex]f(x)=0[/tex] in the function [tex]f(x)=(x-3)^4(x+6)^2[/tex]
Thus, we have,
[tex]$0=(x-3)^{4}(x+6)^{2}$[/tex]
Thus, we have,
[tex]0=(x-3)^{4} \ and\ 0=(x+6)^{2}[/tex]
First solving the expression [tex]$0=(x-3)^{4}$[/tex], we have,
[tex]x=3[/tex] with multiplicity 4.
Also, solving the expression [tex]$0=(x+6)^{2}$[/tex], we have,
[tex]x=-6[/tex] with multiplicity 2.
Thus, the roots of the polynomial function is 3 with multiplicity 4 and –6 with multiplicity 2
Hence, Option d is the correct answer.